2021
DOI: 10.1007/s00330-021-07970-2
|View full text |Cite
|
Sign up to set email alerts
|

Different phenotypes of neuropsychiatric systemic lupus erythematosus are related to a distinct pattern of structural changes on brain MRI

Abstract: Objectives The underlying structural brain correlates of neuropsychiatric involvement in systemic lupus erythematosus (NPSLE) remain unclear, thus hindering correct diagnosis. We compared brain tissue volumes between a clinically well-defined cohort of patients with NPSLE and SLE patients with neuropsychiatric syndromes not attributed to SLE (non-NPSLE). Within the NPSLE patients, we also examined differences between patients with two distinct disease phenotypes: ischemic and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…8 9 In a recent study, we demonstrated that patients with inflammatory NPSLE have reduced brain volumes and increased white matter hyperintensity (WMH) volume compared with other NPSLE phenotypes. 10 Whether structural brain changes in patients with different NPSLE phenotypes are associated with cognitive dysfunction remains to be elucidated.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%
See 1 more Smart Citation
“…8 9 In a recent study, we demonstrated that patients with inflammatory NPSLE have reduced brain volumes and increased white matter hyperintensity (WMH) volume compared with other NPSLE phenotypes. 10 Whether structural brain changes in patients with different NPSLE phenotypes are associated with cognitive dysfunction remains to be elucidated.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%
“…All participants were scanned with a standardised scanning protocol, that included a 3-D T1-weighted scan (voxel size = 1.17 × 1.17 × 1.2 mm 3 ; repetition time (TR)/ echo time (TE) = 9.8/4.6 ms) and a 2-D or 3-D fluid-attenuated inversion recovery (FLAIR) scan. A total of 109 participants were scanned with a 2-D-multislice FLAIR scan (voxel size = 1.0 × 1.0 × 3.6 mm 3 ; TR/TE/ inversion time (TI) = 10 000/120/2800 ms) and 54 participants were scanned with a 3-D FLAIR scan (voxel size = 1.10 × 1.11 × 0.56 mm 3 ; TR/TE/TI = 4800/576/1650 ms) (for more details see 10 ). The change in the FLAIR scan occurred in February 2013.…”
Section: Mri Protocolmentioning
confidence: 99%
“…The potential relevance of WMH shape in the radiological diagnostic process has been already demonstrated in diabetes ( De Bresser et al, 2018 ), cerebral small vessel disease ( Kant et al, 2019 ) and stroke ( Ghaznawi et al, 2021 ). Evidence for ventricular and periventricular structural differences between NPSLE phenotypes, including between NPSLE and non-NPSLE, have been already given, including in our own studies ( Inglese et al, 2021 ), and it is possible that the features detected by the ML algorithm in the NPSLE population is a combined effect of volume and shape characteristics. Finally, there is no consistent reporting on direct involvement of the basal cisterns per se in SLE or NPSLE, barred few case reports ( Kawamata et al, 1991 ; Tsushima and Kubo, 1999 ).…”
Section: Discussionmentioning
confidence: 77%
“…3D T 1 -weighted images were segmented using the CAT12 toolbox from the statistical parametric mapping software to determine total grey matter (GM), white matter (WM), and cerebral-spinal fluid (CSF) volumes ( Inglese et al, 2021 ). Total intracranial volume was calculated as the sum of gray matter, white matter, and cerebral-spinal fluid volumes.…”
Section: Methodsmentioning
confidence: 99%
“…WMH location in patients with arterial diseases can provide prognostic survival information 14 . WMH in SLE patients has not been shown to be homogeneous across subgroups 15 . One study reported that the prevalence of WMH in the splenium of the corpus callosum, in the right superior longitudinal fasciculus and in some small clusters in the right corona radiata was higher in NPSLE patients compared to SLE patients without NP involvement 16 .…”
Section: Introductionmentioning
confidence: 99%